How Serious Is Debt Among Probation Clients? A Study Into the Prevalence and Scope of Debt in a Dutch Probation Sample - Beek, Gercoline van (International journal of offender therapy and comparative criminology, 2022)
Although studies point to a relationship between debt and crime, there is a limited understanding of their reciprocal relationship and possible mediating risk factors. Moreover, knowledge about the prevalence and scope of debt among offenders is lacking. Therefore, the present study analyzed 250 client files including risk assessment data from the Dutch probation service on the prevalence of debt and possibly related risk factors. The results show that debt is highly prevalent and complex, which underlines the importance of acquiring more knowledge about debt as a potential risk factor for relapse during supervision. It was found that problems with regard to childhood and living situation, education and work/daytime activities, and mental and physical health may be possible underlying risk factors in the relationship between debt and crime. These insights can help professionals adequately support clients with regard to debt in order to prevent recidivism.